Determinación de bacterias coliformes totales y fecales del agua del Río Jubones en el sector de la Bocatoma del cantón El Guabo - León Hurtado, Teresita P. (2007)
In our country, the same as other developing one the illnesses caused by bacteria, virus or pathogen protozoa are the risk for the most common and diffused health that it takes I get the drink wAter.